Integrated FMEA and FTA Approaches for Quality Control in False Eyelash Manufacturing - Telma Anis Safitri; Devanda Diar Ananditya; Katon Muhammad; Joni Prayogi (Jurnal Akuntansi, Manajemen dan Ekonomi, 2025)
The synthetic eyelash manufacturing industry in Indonesia, particularly PT Hyup Sung Indonesia (HSI) in Purbalingga, faces ongoing challenges in maintaining product quality due to a high incidence of defects. This study aims to analyze and mitigate production-related risks through the application of Failure Mode and Effects Analysis (FMEA) and Fault Tree Analysis (FTA). FMEA is utilized to systematically identify potential failure modes and prioritize improvement efforts based on the Risk Priority Number (RPN), while FTA is employed to trace the root causes of critical failures in a hierarchical structure. The FMEA results identified three major failure modes with the highest RPN values: knot misalignment during opening (RPN 150), insufficient application of adhesive (RPN 140), and curling of the knot during opening (RPN 140). FTA revealed that these issues primarily arise from equipment-related factors, operator handling methods, and inconsistencies in the oven-setting process. Based on these findings, several corrective actions are proposed, including the replacement of production tools (racks and brushes), installation of automatic timers, standardization of operating procedures, and operator training programs. The implementation of these measures is expected to reduce the risk of production failures and enhance the overall quality of synthetic eyelash products